Cancer worry after facial nonmelanoma skin cancer resection and reconstruction: A 1‐year prospective study. Issue 2 (14th September 2021) - van Hensbergen, Lucy J.; Veldhuizen, Inge J.; Lee, Erica H.; Houterman, Saskia; Brinkhuizen, Tjinta; van der Hulst, René R. W. J.; Hoogbergen, Maarten M.
Abstract: Objective: Nonmelanoma skin cancer (NMSC) is one of the most diagnosed cancers in the world, with the number of new occurrences rising every year. Most patients with facial skin cancer experience cancer‐related worry. Yet, little is known about their worry during the period after cancer treatment. This study aimed to assess the long‐term change of cancer worry after surgical treatment in patients with NMSC. Methods: Patients undergoing surgery for facial NMSC between December 2017 and March 2020 were asked to complete the FACE‐Q Skin Cancer—Cancer Worry scale before (baseline), 3‐month, and 1‐year post‐surgery. Results: A total of 151 patients completed the baseline and 3‐month, and 99 (65.6%) the 1‐year post‐operative survey. A significant decrease in cancer worry score was seen between baseline and 3‐month post‐surgery ( p  < 0.001). No difference was found between the 3‐month and 1‐year post‐surgery scores ( p  = 0.78). Less improvement in cancer worry was seen for patients who had one facial skin cancer in their medical history ( p  = 0.001) and patients who had a history of facial surgery ( p  < 0.001). Conclusion: Post‐surgery patients still experience cancer worry. Therefore, targeted counseling might be of value when coping with cancer‐related concerns. Patients with a history of facial NMSC and patients with a history of facial surgery might benefit from additional counseling.